PRAGMATIC FAILURE TO PRAISE AND PRAISE RESPONSE TO ARABIC AND ENGLISH LEARNERS - Kamsinah; Nurasia Natsir; Nuraziza Aliah; Noerhayati Amirullah; Nurasia Natsir (International Journal of Social Science, 2022)
The aim of this study was to investigate the pragmatic failure in English and Arabic students at the UIN Alauddin Makassar's Faculty of Adab and Cultural Studies. The data for the study were gathered through observation, distribution of questionnaires in the form of a discourse completeness test (DCT), and interviews. Quantitative and qualitative research data were collected in this research. This study employed three statistical models or techniques: descriptive statistics, association rules (a priori algorithm), Chi Square, and qualitative analysis. The results shos that there are three kinds of pragmatic failure that produced by the English and Arabic students such as sociopragmatic, pragmalinguistic, and psychopragmatic aspects. In addition, The researcher suggests to the next researcher to study more deeply about the types of pragmatic failure in other fields.